New species of Afagrilaxia Bílý & Bellamy, 1999 (Coleoptera: Buprestidae) from South Africa - Obořil, Martin; Sekerka, Lukáš (Zootaxa, 2025)
Afagrilaxia magorgori Obořil & Sekerka, sp. nov. from South Africa and Zimbabwe is described, illustrated, and compared with the yet only known species of the genus, Afagrilaxia natalensis (Bellamy, 1986), which is also illustrated.